PENGARUH KETERLIBATAN KERJA, PERSON-ORGANIZATION FIT (P-O FIT), PEMBELAJARAN ORGANISASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA (STUDI PADA PEGAWAI DINAS SOSIAL PROVINSI JAWA TENGAH) - Devi Widya Anggraeni, 10.05.51.0022; Suko Priyono, Bambang (Students Journal of Economic and Management, 2014)
The study analyzed the influence of Employee Engagement, Person-Organization FitÂ Â Â (P-O Fit), Organizational Learning and Organizational Commitment to Performance. The research object in this paper is the Social Department in Central Java Province. Sampling technique in this study is the use of data or entire employee population by using the method of data collection questionnaire (questionnaire) by distributing a list of statement to the respondents in order to obtain information. The purpose of the study was formulated to look for answers that affect Employee Performance. The data were analyzed using the data to the normality test variable regression model gadfly or residuals have a normal distribution, the classical assumption of multicolinearity test to test correlation between the independent variables, factor analysis to test the validity of the question items, cronbach alpha to test the reliability of the instrument, regression analysis, to examine the influence of the partial of each independent variable was tested with the coefficient of determination (R2), F test and t test model to test and prove partial effect of each independent variable. The results of the research are: (1) Employee Engagement has a positive and significant impact on Employee Performance. (2) Person-Organization Fit (P-O Fit) has a positive and significant impact on Employee Performance. (3) Organizational Learning has a positive and significant impact on Employee Performance. (4) Organizational Commitment has a positive and significant impact on Employee Performance. Keywords: Variable Employee Engagement, Person-Organization Fit (P-O Fit), Organizational Learning, Organizational Commitment, Performance